Perbuatan Melawan Hukum (PMH) Sebagai Perikatan Yang Lahir Karena Undang-Undang: Implikasi Terhadap Penentuan Ganti Rugi - Febriansyah, Raafid; Kurniawan, Zhufar Athalla; Syahladin, Firny Ramadina; Larasati, Giaby Amanda; S, Surahmad (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Unlawful acts are an obligation arising from the law and their impact on determining compensation. In an increasingly complex era of globalization, individuals are often involved in cooperation that requires a strong understanding of the law of obligations regulated in the Civil code. The legal relationship between the parties must be legally recognized by fulfilling the requirements for the validity of the agreement. The purpose of this study is to analyze how to determine the amount of compensation arising from Unlawful Acts, as well as the variables that influence the application of the principle of propriety in court decisions. By using a normative legal approach, this study found that determining compensation requires four important elements: the existence of an Unlawful Act, losses, a causal relationship between the loss and the Unlawful Act, and an error by the party committing the Unlawful Act. These findings are expected to contribute to legal practice and the court's handling of cases related to Unlawful Acts.